Effect of Coloading Fluid on The Incidence of Post Operative Nausea and Vomiting (PONV) in Patients Post Spinal Anesthesia : A Study at RSUD Wates - Hubabillah, Fauziyyah; Rosidah, Istiqomah; Azizah, Aisyah Nur (Adult Health Nursing Journal, 2025)
Introduction:  Surgery with spinal anesthesia can lead to complications such as nausea and vomiting due to hemodynamic imbalances during and after anesthesia. Perioperative fluid status plays a crucial role in maintaining patients' hemodynamic balance during surgery. One fluid management strategy that can be implemented is co-loading fluid therapy. Objectives: This study aims to determine the effect of co-loading fluid on the incidence of Post Operative Nausea and Vomiting (PONV) in patients after spinal anesthesia at RSUD Wates. Methods: This research employed a quantitative method with a quasi-experimental design. The study design used was a two-group posttest only. The sampling technique utilized non-probability sampling with consecutive sampling, resulting in 36 respondents according to inclusion and exclusion criteria. Data collection was conducted using observation sheets, and data processing in this study utilized the Mann-Whitney test. Results:  Data analysis using the Mann-Whitney test yielded a p-value of 0.015 (p < 0.05), indicating that the alternative hypothesis (Ha) is accepted. This result shows that there is an effect of co-loading fluid therapy on the incidence of Post Operative Nausea and Vomiting (PONV) in patients undergoing spinal anesthesia at RSUD Wates. Conclusions:  There is an effect of co-loading fluid therapy on the reduction of Post Operative Nausea and Vomiting (PONV) in patients after spinal anesthesia at RSUD Wates.